ROLE OF TAKRA ODAN AS AHAR ALONG WITH NAGKESHAR CHURNA IN PREVENTION AND MANAGEMENT OF SHWETAPRADARA - Minal P. Mawale; Sanket V. Pajai (International Journal of Ayurveda and Pharma Research, 2020)
Leucorrhoea i.e. Shwetapradar is universal problem of women which is caused by increased stress, strain, improper diet & unhygienic conditions. Most commonly used treatment according to modern science is vaginal pessaries which act fast & give symptomatic relief but they have chances of recurrence. Ayurveda advocates healthy lifestyle including proper diet & treatment regime to manage such diseases & its recurrence. According to Ayurveda Ahar is the main reason for being healthy or diseased. Considering this, a clinical study has been planned with an aim of to evaluate the role of Takra & Odan as Ahar along with Nagkeshar churna in Shwetapradar.For the study, 60 patients having symptoms of Shwetapradar were selected & divided in two groups randomly. Trial group (Group A) was treated with Nagkeshar churna along with Takra & Odan as Ahar whereas control group (Group B) was treated with Nagkeshar churna alone for 21 days with weekly follow up. After the completion of study it was observed that relief obtained in symptoms was faster in Group A than in Group B. Also relief obtained was much more in Group A than in Group B. Hence study was concluded that the formulation stimulates astringent action in vaginal mucosa and reduces excessive vaginal discharge & pelvic congestion. Thus dietary modifications play a significant role in curing Shwetapradar.